2009
DOI: 10.1183/09031936.00049909
|View full text |Cite
|
Sign up to set email alerts
|

Lung function predicts lung cancer risk in smokers: a tool for targeting screening programmes

Abstract: ABSTRACT:The relationship between smoking, lung cancer and airflow obstruction is recognised but it is unclear whether the presence of minimal lung function damage constitutes an independent risk factor for the development of lung cancer.In order to identify those individuals at higher risk of lung cancer on the basis of functional impairment, we evaluated baseline pulmonary function tests of 3,806 heavy smokers undergoing annual chest computed tomography screening, and compared the forced expiratory volume in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 40 publications
5
67
0
Order By: Relevance
“…In a second analysis (Figure 2), we found that this linear relationship extended to smokers meeting GOLD U and restrictive spirometry (4, 23) with a magnitude comparable to those with airflow limitation of GOLD 1-2 severity. This study also shows that, not only is a reduced expiratory flow rate an important risk variable for developing lung cancer among heavy smokers, it is also one of the most important risk variables relative to those of age and pack-years (Tables 1 and 2, Table E3) (1,2,5,8,24). This suggests that airflow limitation represents a global barometer of susceptibility to the key smoking-related lung diseases, including lung cancer (25).…”
Section: Original Research Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In a second analysis (Figure 2), we found that this linear relationship extended to smokers meeting GOLD U and restrictive spirometry (4, 23) with a magnitude comparable to those with airflow limitation of GOLD 1-2 severity. This study also shows that, not only is a reduced expiratory flow rate an important risk variable for developing lung cancer among heavy smokers, it is also one of the most important risk variables relative to those of age and pack-years (Tables 1 and 2, Table E3) (1,2,5,8,24). This suggests that airflow limitation represents a global barometer of susceptibility to the key smoking-related lung diseases, including lung cancer (25).…”
Section: Original Research Discussionmentioning
confidence: 94%
“…Over the past 30 years, both cross-sectional and prospective studies have consistently shown that the presence of chronic obstructive pulmonary disease (COPD), characterized by irreversible airflow limitation and reduced expiratory flow rates, confers a greater risk of lung cancer (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). This association is independent of smoking history and, strongest when COPD is defined by spirometry with the control group confirmed to have normal lung function (1,4,5).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The high proportion of patients with COPD developing lung cancer is not solely related to the common risk factor of cigarette smoking. COPD patients are at increased risk of developing lung cancer, irrespective of their smoking history [6][7][8]. Smokers with airflow obstruction have a five-fold increased risk of lung cancer compared to those with normal lung function [4].…”
Section: Introductionmentioning
confidence: 99%